Towards Inclusive Knowledge Organizational Systems for Multilingual Communities and Conceptual Models in Federal Universities Libraries in Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Knowledge organization systems (KOS)—including classification schemes, subject heading lists, thesauri, and metadata frameworks—remain predominantly monolingual and shaped by epistemological traditions developed in Anglo-American and European contexts, posing significant access barriers for multilingual communities served by academic libraries in linguistically diverse nations such as Nigeria. This paper examines the conceptual and practical challenges of designing inclusive KOS for multilingual users within Nigerian higher education institutions, where English serves as the official language of instruction alongside numerous indigenous languages spoken by students, researchers, and host communities. Drawing on the literature on classification theory, multilingual subject access, indigenous knowledge organization, international library policy instruments, and the technological context of Nigerian academic libraries, this paper proposes a layered conceptual model—the Inclusive Multilingual Knowledge Organization (IMKO) framework—that integrates terminology mapping, parallel vocabularies, community-informed indexing, and adaptive metadata layers within existing library systems. The framework is examined against the operational realities of a composite Nigerian academic library, including its predominant reliance on the Koha open-source integrated library system (ILS), highlighting infrastructural, financial, and human-resource considerations documented in prior research. The paper concludes with recommendations for library and information science education, professional bodies, and policy actors—including the National Universities Commission and the Tertiary Education Trust Fund—to support the gradual adoption of more linguistically inclusive cataloguing and classification practices.